Management Information systems. 2nd edi. - Jawadekar, W. S. (Tata McGraw Hill pub.co.ltd.New Delhi., 2005)
Computer
sent to computer dept.Dt.29/5/06.
ENGLISH
Keywords: Management Information systems. 2nd edi; Computer; Computer